Pengelolaan Pendidikan Dasar Dikaitkan dengan Mobilitas Sosial - Maya Muizatil Lutfillah; Arita Marini; Maratun Nafiah (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2022)
The educational system as a social media needs to change shortly as the society changes or vice versa. The changes in education should bring about improvement in the social life. The history have proved the linkages and close relationship between education on the one hand and the other social circumstances. From this, people can learn that social life in one period is determined by the education system that applied. Conversely, social educational system is strongly influenced by the style and circumstances that shape society. It looks that the relation between education system and the condition of a society which supports that system is a dilemma that tends to be static, because they both affect each other. This is because, on the one hand, education creates driving forces for progress and on the other hand, the community is a decisive force of civilization and knowledge and gives patterns and determine their own course of development and progress.